RESPONS SISWA TERHADAP BUKU LATIHAN AKM STATISTIKA SEBAGAI MEDIA PEMBELAJARAN - Rahmawati, Shela; Khuzaini, Nanang (FKIP Universitas Al Washliyah Medan, 2024)
Technology plays a significant role in advancing education as it facilitates educators in teaching abstract subjects that are difficult to understand, such as mathematics. Mathematics is a key component of human intellectual capability and the revolution of scientific knowledge. In mathematics learning, without engaging teaching media, students tend to disregard the teacher's explanations, become passive, get bored quickly, and merely take notes on the presented material. Therefore, innovative learning media, such as interactive math comics, need to be developed. This study aims to determine students' responses to the use of AKM practice books in mathematics learning. This research is descriptive and focuses on the level of student satisfaction with the learning process using AKM practice books. Students' responses were collected using a Likert scale questionnaire and then analyzed using data categorization techniques. The results of the study indicate that trial results in both small-scale and large-scale classes showed an average rating of very good. Consequently, the AKM practice book is considered practical to use as it received positive feedback from students, being highly useful in the learning process. The AKM practice book, as a mathematics learning medium, significantly aids in the learning process due to its attractive design, easily understandable question texts, clearly explained content, and it makes students feel happy and very interested. Thus, the response of class X8 students at SMA N 1 Sedayu towards the AKM practice book on statistical material is positive and practical for use.